Compliance of Healthcare Workers with Hand Hygiene Practices in the Northeast of Iran: An Overt Observation - Reza Vafaei Nezhad; Atieh Yaghoubi; Kiarash Ghazvini (International Journal of Public Health Science (IJPHS), 2018)
Hand hygiene (HH) is one of the most effective methods to prevent transmission and spread of microorganisms from one patient to another, also, it used to reduce the spread of pathogens in clinical settings and to help control outbreaks but compliance is usually poor. The purpose of this study was to analyze the compliance of hand hygiene and affecting factors among healthcare workers (HCWs) of northeast hospitals in Iran. This study was conducted based on observation method for the compliance of hand hygiene according to the World Health Organization (WHO) guidelines. HCWs were observed during routine patient care in different shifts, also the technique of hand hygiene was assessed through hand washing with alcohol-based disinfectant. Data were collected during 1 year, from June 2014 to July 2015 by the infection control teams in the northeast hospital of Iran. By direct observation, we evaluated a total of 92518 hand hygiene opportunities from 29 hospitals in the northeast of Iran during 1 year, with overall compliance rates in these hospitals were 43.42%. Compliance rates differed by role: nurses43%, doctors 19 % and other health workers 29%. In this observational study, we identified that adherence to hand hygiene practice and use of alcohol-based disinfectant was very low in this hospitals, so effective intervention programs to promote adherence to hand hygiene and use of disinfectants could be effective to increase compliance.